PENGARUH MODEL KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) BERBASIS EDUCAPLAY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Rafael Kukuh Avethresando; Dayu Rika Perdana; Siti Nuraini; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study is the low learning outcomes of Pancasila Education among fourth-grade students at SD Negeri 2 Gondang Rejo. This study aims to analyze the effect of the cooperative learning model of the Teams Games Tournament (TGT) type based on Educaplay media on students' Pancasila Education learning outcomes. Data were collected using test and non-test techniques, with the test instrument consisting of 14 valid items and a reliability value of 0.637. Data analysis was conducted using the Shapiro-Wilk normality test, Levene's Test for homogeneity, and simple linear regression hypothesis testing with SPSS version 27. The results indicate a significant effect of the TGT cooperative learning model based on Educaplay on the Pancasila Education learning outcomes of fourth-grade students at SD Negeri 2 Gondang Rejo in the 2025/2026 academic year, with a significance value of 0.001 < 0.05 and a contribution of 50.4% to student learning outcomes.